PENGARUH TEKNOLOGI INFORMASI TERHADAP EFEKTIVITAS ORGANISASI DI SEKRETARIAT DPRD KABUPATEN KEPULAUAN SULA PROVINSI MALUKU UTARA - UMAR, RAHMAT; ROMPAS, WILSON; POMBENGI, JERICHO DANGA (Sam Ratulangi University, 2017)
Abstract : The purpose of this study was to determine the influence of information technology onorganizational effectiveness in the Secretariat of DPRD Kabupaten Sula Islands of North Maluku Province.This research uses quantitative method. Information technology variables are measured using computerhardware indicators, computer software, information and communication networks, databases. While thevariable of organizational effectiveness is measured using production indicator, efficiency, flexibility andorganizational adaptation. The sample of the research respondents was taken with a simple randomsampling technique of 35 people (25 employees of the Secretariat, DPRD and 10 DPRD members). Datacollection using questionnaire / questionnaire and assisted with interview guide technique. Analyticaltechniques used are inferential statistical analysis of linear regression and product moment correlation. Theresults of data analysis show: (1) regression coefficient variable of information technology to organizationaleffectiveness is positive and significant. (2) correlation coefficient and coefficient of determination ofinformation technology variable to organizational effectiveness is strong and significant. Based on theresults of the study concluded that information technology has a positive effect and has a significant degreeof correlation to organizational effectiveness. Based on the conclusion of this study, it is recommended that:(1) Information technology in Secretariat of DPRD of Sula Islands Regency needs to be improved both inquantity and quality, especially hardware and software, network and communications system and database.(2) The knowledge and skills of employees in the operation of information technology (computerapplications) need to be improved through training. (3) DPRD members also need to have knowledge andskills in the use of information technology (computer applications) for ease of task implementation.Keywords: Information Technology, Organizational Effectiveness.